Interface-induced face-on orientation of the active layer by self-assembled diblock conjugated polyelectrolytes for efficient organic photovoltaic cells. Issue 47 (17th November 2016) - Zhou, Dan; Cheng, Xiaofang; Xu, Haitao; Yang, Hanjun; Liu, Huimin; Wu, Feiyan; Chen, Lie; Chen, Yiwang
Abstract : The self-assembled diblock CPEsPFEO - b -PTNBr andPFEO - b -PTImBr can partially induce a favorable face-on orientation of the active layer. Abstract : Systematic investigation of the instinctive self-assembly of diblock conjugated polyelectrolytes (CPEs) as electron transport layers (ETLs) on the arrangement and morphology of the upper active layer in polymer solar cells (PSCs) is usually ignored. The two water/alcohol-soluble diblock CPEs with different terminal ionic groups, PFEO - b -PTNBr andPFEO - b -PTImBr, offer an ohmic contact between the ITO electrode and the active layer by substantially reducing the work function of ITO via modulation of the interfacial dipoles. More intriguingly, the spontaneous self-assembly of the diblock polymers causes an ordered scolopendra-like conformation to develop on the ITO cathode. These self-assembled diblock CPEs can act as a template to further partially induce a preferable face-on orientation of the donor component. Surprisingly, n-type self-doping is observed in the two CPEs based on the p-type conjugated backbone, particularly inPFEO - b -PTImBr with imidazolium salt. As a result, the power conversion efficiencies (PCEs) of the devices based on PTB7-Th:PC71 BM are remarkably enhanced to 9.0% forPFEO - b -PTNBr and 9.4% forPFEO - b -PTImBr . Intriguingly, both ZnO/PFEO - b -PTNBr and ZnO/PFEO - b -PTImBr based PTB7-Th:PC71 BM devices exhibit superior PCEs compared to that of the classical published and commonly used PFN (8.42%) and PFNBr (8.38%) ETLs based devices. These results indicate that the development of self-assembled diblock CPEs opens a new point of view and provides a straightforward approach to achieve high performance polymer solar cells by simultaneously modulating the morphology of the interlayer, active layer and interfacial work function.